Αγάπη μου συρρίκνωσα τον ανδρισμό σου: Ετεροκανονικότητα και ομοερωτική επιθυμία εντός του κοινωνικού θεσμού του γάμου - Ιωαννίδου Όλγα (Aegean Working Papers in Ethnographic Linguistics, 2017)
This paper investigates the dialectical relationship between language, gender and sexuality and the way it is realized in discourse production based on data collected from interaction within a community of practice. The goal is to highlight how discourse indexes both gender and sexuality, while, at the same time, a “coming out” event –taking place in a social institution such as marriage– subverts heteronormal presuppositions. The four interlocutors (men and women) perform their gendered and sexual self, revealing –each one of them– features of their identity intermediated not only by language and identity but by heteronormative ideologies of the contemporary Greek reality. Depending on the situation, the particular individuals do not hesitate either to react to anything that offends the normality of that reality or to defend the dynamics of the desire that determines the fluidity of their own sexuality.